Analysis of the National Character Value of Ahl Al-Sunnah Wa Al-Jamâ'ah students at the LP Ma'arif PCNU Wonosobo, Central Java, Indonesia - Ngarifin Shidiq; Abdul Majid; Sri Haryanto; Ahmad Khoiri; Denok Sunarsi (JTP - Jurnal Teknologi Pendidikan, 2019)
Character education is very important to be developed in maintaining the character of a civilized nation. so that the research objective is in the implementation of character education in LP Ma'arif NU Wonosobo, Central Java, Indonesia. descriptive-interpretive research methods related to the implementation and development of national character values ​​in the LP Ma'arif PCNU Wonosobo environment. The results showed: First, character values ​​require the Indonesian people to always implement and obey the basic values ​​of Pancasila, this can be reflected in the daily behavior of society. Second, the characteristics of the Ahl al-sunnah wa al-jama'âh curriculum are based on three main values, namely: (a) basic principles (b) the character of the ukhuwwah nahdliyah, and (c) the character of the mabâdi 'khairu ummah. Third, the development and internalization of the national character values ​​in the LP Ma'arif PCNU Wonosobo environment is carried out through the Ahl al-Sunnah wa al-Jamâ'ah subject which is intended to develop values ​​that come from Islam, Pancasila, culture and educational goals national